Karakteristik Pelayanan Angkutan Kota di Kota Palu (Studi kasus: Pelayanan Angkutan Kota di Universitas Tadulako) - Suryani, Sri; Ismadarni, Ismadarni; Batti, Joy Fredi (Jurusan Teknik Sipil Universitas Tadulako, 2015)
Nowadays, students are less interested in using public transportation to the University of Tadulako.One reason is the travel time to arrive on campus can not be predicted. This study aims to determine the characteristics of urban transport users in serving the student travel, especially in Tadulako University.Â The researc were conducted using descriptive method. The research was carried on by distributing questionnaires to 131 respondents. The respondents are the city transport users who travel to Tadulako University. The results of the research and analysis shows that the ease of getting public transportation to travel to and from the University of Tadulako classified as difficult, so users should walk or using the motorcycle taxi (ojek) to get to the waiting place for public transportation. There are areas frequented by the public transportation so that users can negotiate several times and there are also certain regions where users can only do 1 time negotiations within the same time frame. The uncertainty of travel routes makes the travel time of user to the destination is unpredictable.